FORMULATION OPTIMIZATION AND CHARACTERIZATION OF GANCICLOVIR LOADED DRY CHITOSAN NANOPARTICLES - Patel, Rutu; Patel, Gayatri; Gajra, Balaram; Parikh, RAJESH (Asian Journal of Pharmaceutical and Clinical Research, 2017)
ABSTRACT Objective: The objective of this work was to formulate, optimize, and characterize ganciclovir (GCV) loaded dry chitosan nanoparticles (CSNPs). Methods: The GCV loaded CSNPs was prepared by ionic gelation method. Box–Behnken design was employed to optimize the influence of independent process and formulation variables like drug to polymer ratio, concentration of sodium tripolyphosphate, and stirring time (min) on the dependent variables such as particle size (PS) and drug encapsulation efficiency (% EE). The optimum conditions were determined by regression analysis of the output data. Results: The independent variables had interactive effects and they affected both the responses. The optimum formulation had PS within the range of 100-120 nm and % EE between 85% and 86%. The prepared GCV loaded CSNPs were dried by fluidized bed drying method. Fourier transform infrared spectra showed there was no physicochemical interaction between GCV and CS. Powder X-ray diffraction study showed less intense crystalline peaks indicated that GCV may exist in the formulation as amorphous nanodispersion or molecular dispersion form. Differential scanning calorimetry study was performed which indicated that the drug was molecularly dispersed inside the matrix of CS. Higuchi model was the best to fit the in vitro release data for the GCV loaded CSNPs. Conclusion: From the results, it can be concluded that the GCV loaded dry CSNPs were formulated, optimized, and characterized using desired pharmacotechnical properties. Keywords: Chitosan nanoparticles, Box–Behnken design, Sodium tripolyphosphate, Ionic gelation.